Natural orifice transvaginal endoscopic surgery myomectomy: An innovative approach to myomectomy - Chyi-Long Lee; Chen-Ying Huang; Kai-Yun Wu; Yu-Feng Hu; Chih-Feng Yen; Chien-Min Han (Wolters Kluwer Medknow Publications, 2014)
Objective: This study aims to describe the feasibility of treating uterine leiomyoma with myomectomy by natural orifice transvaginal endoscopic surgery (NOTES). Materials and methods: Women with leiomyoma underwent myomectomy by transvaginal NOTES in a tertiary referral medical center and surgical outcomes were measured. Results: Three patients underwent the surgery at a mean age of 46.7 [standard deviation (SD), 6.2] years and mean body mass index of 21.6 (SD, 2.1) kg/m2. The average operative time was 128 (SD, 55) minutes. The average blood loss in the operation was 317 (SD, 207) mL without blood transfusion. No intra- or postoperative complications were noted. No cases were converted to traditional laparoscopy or laparotomy. Conclusion: Our preliminary results showed the safety and feasibility of transvaginal NOTES in laparoscopic myomectomy. It is one of the minimally invasive surgeries and results in scarless healing. However, it should be evaluated in more cases.